Malignancies of the female genital tract from general gynecological services: Five years review at BPKIHS - Pokharel, Hanoon P; Basnet, Nibedita; Uprety, Dhruba; Bannerjee, Basudeb; Sinha, Aravind; Pokharel, Paras K (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To observe the trend of malignant diseases of the female genital tract, and to assess pattern amongst the diagnosed cases and its management at BPKIHS. Methods: All the diagnosed cases of female genital malignancies were followed. Cases in advance stages were referred to Oncology Centers. Some patients opted to undergo treatment at BPKIHS. Those case sheets and histopathology reports were analyzed to see the trend and pattern of diseases and its optimum management. Referred cases who came for further follow up in the general gynecology department after consultation and treatment are also included in the study. Setting: Department of obstetrics & Gynecology and Pathology, BPKIHS. Results: Cervical cancer was the commonest malignant disease 216 (67.3%) followed by the ovary (17%), endometrium (10%), choriocarcinoma (3.4%) and vulva and vagina (2.8%). The mean (years in) age of the patients varied with the type of cancer as follows - cervix (30.9), ovary (40.4), endometrium (54.8), choriocarcinoma (25.6) and Vagina & vulva (42.2). Out of the total 216 patients Carcinoma Cervix only 20 patients were admitted for Radical surgery and treatment. 196 patients belonged to the group of advanced carcinoma cervix and were referred to the cancer hospital for radiotherapy and chemotherapy. Conclusion: Cancer cervix is the most common and manageable disease if diagnosed early provided mandatory selective screening program are implemented. The missed opportunity to diagnose the disease in time should be utilized by creating national or regional community - based cervical cancer screening program. General gynecological service provider can also contribute a lot to reduce the burden of disease. Keywords: Female genital malignancies, carcinoma cervix, radiotherapy and chemotherapy. doi:10.3126/njog.v2i1.1474 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 35 - 38 May -June 2007